E. coli Cell Lysis Induced by Lys394 Enzyme Assisted by Magnetic Nanoparticles Exposed to Non-Heating Low-Frequency Magnetic Field - Azizbek D. Usvaliev; Natalia G. Belogurova; Konstantin V. Pokholok; Alexander V. Finko; Andrey N. Prusov; Dmitry Yu. Golovin; Konstantin A. Miroshnikov; Yuri I. Golovin; Natalia L. Klyachko (MDPI AG, 2023)
The spreading of microbial pathogens with more and more resistance to traditional low-molecular antibiotic agents demands new approaches to antibacterial therapy. The employment of bacteriophage enzymes capable of breaking bacterial cell walls has attracted much interest within this context. The specific features of the morphology of Gram-negative bacteria prevent the effective direct usage of lytic enzymes and require assistance from additional helpers to facilitate cell lysis. The current work is devoted to the study of boosting the lysis of Escherichia coli (E. coli) JM 109 and MH 1 strains induced by Lys394 bacteriophage endolysin by means of rod-like (56 × 13 nm) magnetic nanoparticles (MNPs) activated by a non-heating low-frequency magnetic field (LF MF) with a frequency of 50 Hz and a flux density of 68.5 mT in a pulse-pause mode (1 s on and 0.3 s off). According to theoretical assumptions, the mechanism of MNP assistance is presumably based upon the disordering of the outer membrane that facilitates enzyme permeation into peptidoglycans to its substrate. It is found that the effect of the LF MF reaches an almost a twofold acceleration of the enzyme reaction, resulting in almost 80 and 70%, respectively, of lysed E. coli JM 109 and MH 1 cells in 21 min. An increase in the membrane permeability was proven by two independent experiments employing β-lactamase periplasmic enzyme leakage and Nile Red (NR) hydrophobic dye fluorescence. It is shown that the outer membrane disordering of E. coli caused by exposure to LF MF nanoparticle movement leads to almost complete (more than 80%) β-lactamase release out of the cells' periplasm to the buffer suspension. Experiments with NR (displaying fluorescence in a non-polar medium only) reveal a drastic reduction in NR fluorescence intensity, reaching a change of an order of magnitude when exposed to LF MF. The data obtained provide evidence of changes in the bacterial cell wall structure. The result shown open up the prospects of non-heating LF MF application in enhancing enzyme activity against Gram-negative pathogens.